Optimalisasi Pemanfaatan Teknologi Augmented Reality Sebagai Media Pembelajaran Interaktif: A Systematic Literature Review - Semara, Weda (Universitas Negeri Surabaya, 2026)
The rapid advancement of digital technology has encouraged various innovations in education, including the use of Augmented Reality (AR) as an interactive learning medium. This study aims to systematically review the utilization of Augmented Reality in educational contexts and its contribution to improving learning effectiveness and quality in the digital era. This research employs a Systematic Literature Review (SLR) method based on the PRISMA guidelines. Article searches were conducted using the Publish or Perish application with Google Scholar as the database, followed by a screening process using Covidence based on predefined inclusion and exclusion criteria. A total of 29 selected articles were analyzed using qualitative descriptive analysis and bibliometric analysis with the support of VOSviewer. The findings indicate that Augmented Reality has a positive impact on students’ conceptual understanding, learning motivation, and engagement, particularly in science, mathematics, and STEM education. However, several challenges remain, including increased cognitive load, limited technological infrastructure, and teachers’ readiness to integrate AR into learning activities. Therefore, the optimization of Augmented Reality in education should be implemented holistically by considering pedagogical approaches, instructional design, and the readiness of the educational ecosystem.